2017
DOI: 10.1038/ncomms15761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary PET imaging of 11C and 18F isotopologues of the ROS1/ALK inhibitor lorlatinib

Abstract: Lorlatinib (PF-06463922) is a next-generation small-molecule inhibitor of the orphan receptor tyrosine kinase c-ros oncogene 1 (ROS1), which has a kinase domain that is physiologically related to anaplastic lymphoma kinase (ALK), and is undergoing Phase I/II clinical trial investigations for non-small cell lung cancers. An early goal is to measure the concentrations of this drug in brain tumour lesions of lung cancer patients, as penetration of the blood–brain barrier is important for optimal therapeutic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…For instance, the poor CNS permeation of TKIs is now accepted as a determinant of the poor response of CNS malignancies, including brain metastasis, to this class of molecularly targeted therapy (Holohan et al, 2013;Camidge et al, 2014). PET using radiolabeled analogs of TKIs can be regarded as a useful method to compare their CNS penetration in humans (Verheijen et al, 2017) and non-human primates, a relevant animal model of the human BBB (Ballard et al, 2016;Collier et al, 2017aCollier et al, , 2017b. Virtually all members of the clinically important class of TKIs were identified as dual P-gp/BCRP substrates, which provides a mechanistic explanation for their low brain penetration (Agarwal et al, 2011;Durmus et al, 2015).…”
Section: Pharmacokinetic Imaging To Study the Fate Of Drugs At The Simentioning
confidence: 99%
“…For instance, the poor CNS permeation of TKIs is now accepted as a determinant of the poor response of CNS malignancies, including brain metastasis, to this class of molecularly targeted therapy (Holohan et al, 2013;Camidge et al, 2014). PET using radiolabeled analogs of TKIs can be regarded as a useful method to compare their CNS penetration in humans (Verheijen et al, 2017) and non-human primates, a relevant animal model of the human BBB (Ballard et al, 2016;Collier et al, 2017aCollier et al, , 2017b. Virtually all members of the clinically important class of TKIs were identified as dual P-gp/BCRP substrates, which provides a mechanistic explanation for their low brain penetration (Agarwal et al, 2011;Durmus et al, 2015).…”
Section: Pharmacokinetic Imaging To Study the Fate Of Drugs At The Simentioning
confidence: 99%
“…Lorlatinib has been specifically developed for improved CNS penetration (26). To assess CNS penetration of lorlatinib noninvasively, 11 C and 18 F isotopologues of lorlatinib were developed (27). 11 Clorlatinib administered to nonhuman primates showed that CNS uptake of 11 C-lorlatinib peaked at 10 min after injection, with the highest uptake being in the cerebellum (27).…”
Section: Alk Inhibitorsmentioning
confidence: 99%
“…To assess CNS penetration of lorlatinib noninvasively, 11 C and 18 F isotopologues of lorlatinib were developed (27). 11 Clorlatinib administered to nonhuman primates showed that CNS uptake of 11 C-lorlatinib peaked at 10 min after injection, with the highest uptake being in the cerebellum (27). Tumor imaging in a human EML4-ALK-positive NSCLC xenograft mouse model showed that tumor uptake (2.2%-2.4% injected dose per gram of tissue) could be blocked by adding unlabeled lorlatinib (,0.4% injected dose per gram of tissue) (27).…”
Section: Alk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[81,132,133,[135][136][137][138][139][140][141][142][143] It is noteworthy that [ 18 F]FPEB synthesized by the SCIDYm ethod was fully automated, thereby resulting in asubstantial improvement (3-10 fold) in the RCY and molar activity compared with the traditional S N Ar method. [81,132,133,[135][136][137][138][139][140][141][142][143] It is noteworthy that [ 18 F]FPEB synthesized by the SCIDYm ethod was fully automated, thereby resulting in asubstantial improvement (3-10 fold) in the RCY and molar activity compared with the traditional S N Ar method.…”
Section: Angewandte Chemiementioning
confidence: 99%